Levofloxacin (Oftaquix) a fluoroquinolone of a new generation in prevention of the postoperative endophthalmitis following uncomplicated cataract surgery – the study of the European Society of Cataract and Refractive Surgeons (ESCRS) - Izdebska, Justyna; Szaflik, Jacek (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Randomised multi-centre european clinical trial of antibiotic prophylaxis for endophthalmitis following cataract surgery – study has just begun in Poland. Poland is joining one of the largest prospective european clinical study of antibiotic prophylaxis and the largest in ophthalmology – the ESCRS endophthalmitis prophylaxis clinical trial. Up to 35 000 cataract patients are going to be recruited for this randomized, controlled, multi-centre study in 16 centres from 10 european countries. The goal is to reduce the incidence of endophthalmitis after cataract phacoemusification in Europe to less than 0.05% (less than 1 per 2 000 surgeries). The patients will be divided into four groups; different regimes of two antibiotics: cefuroxime injected intra-camerally and levofloxacine eye drops topically will be compared.